URBAN FARMING BERBASIS AKUAPONIK PADA LAHAN SEMPIT SEBAGAI ALTERNATIF KETAHANAN PANGAN DI MASA DEPAN - Pebriani, D.A.A.; Saraswati, N.L.G.R.A.; Atmaja, P.S.P.; Dewi, A.P.W.K.; Ernawati, N.M.; Julyantoro, P.G.S.; Indrawan, G.S.; Darmendra, I.P.Y.; Negara, I.K.W. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana MengabdiDO - 10.24843/BUM.2025.v24.i02.p14, 2024)
Musi Village is one of the areas in Gerokgak Subdistrict with a large number of migrants and has felt the impact of the covid-19 pandemic. The background of the people of Musi Village, most of whom work as farmers and fish farmers, makes urban farming with an aquaponic system a very suitable activity to be applied. This farming activity is a combination of raising fish and aquatic plants that have economic value. The integration of tilapia and pakcoy rearing can be done simultaneously so as to provide added value for farmer. The purpose of this activity is to provide information and skills for the people of Musi Village about aquaponic-based urban farming methods on narrow land as one solution to meet family needs and even the results can be commercialized so as to improve economic conditions.The activity was carried out on August 19, 2023 at the Musi Village Hall, Gerokgak District, Buleleng Regency which was attended by the Fish Farmer / Fisherman Group, Farmers Group, and Women Farmers Group. This activity was integrated with KKN activities that took place at the same time. Participants were very enthusiastic about listening to the material from 2 speakers, namely Mr. I Kadek Suparta and Dr. Pande Gde Sasmita Julyantoro, S.Si., M.Si. The participants were very enthusiastic about participating in the activity. At the end of the activity, a plaque was handed over to the keynote speaker.